A bibliometric study of the pediatric inguinal hernia publication landscape from the web of science database - Anjan Kumar Dhua; Mohit Garg; Ashwani Kumar Mishra; Prabudh Goel; Vishesh Jain; Devendra Kumar Yadav (Wolters Kluwer Medknow Publications, 2022)
Background: The number of times a research work gets cited by another article is one of the article-level metrics for assessing the quality of a research publication. Citation analysis by bibliometric review has been performed in several disciplines. The current study was aimed to systematically review the literature available on pediatric inguinal hernia since 1960 in terms of the 25 most cited articles in this field and analyze the bibliometric variables author and organizational collaborative patterns. Methods: Thomson Reuters Web of Science citation indexing database and research platform were used to retrieve the most cited articles in pediatric inguinal hernia (PIH) using appropriate search strings. The characteristics (name of authors, the total number of authors, the title of publication, journal of publication, year of publication, etc.) of the 25 top-cited articles were recorded. Specific bibliographical parameters were derived and analyzed. Visualization maps were generated using VOSviewer software. Results: The analysis revealed that the Journal of Pediatric Surgery was leading the choice of journal for publication. While most of the publications originated from the United States of America, Schier was the most influential author. Five of the eight top-productive authors are also the most connected. Conclusion: Articles on laparoscopic repair in PIH have been heavily cited. Following the United States of America, Turkey stands out as the topmost productive country in PIH. The publications on PIH show that "collaboration" is the bridging force between productivity and influence on the academic community.